2021
DOI: 10.1093/molbev/msab075
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of an Enhanced POU Reprogramming Factor for Cell Fate Engineering

Abstract: Transcription factor-driven cell fate engineering in pluripotency induction, transdifferentiation, and forward reprogramming require efficiency, speed, and maturity for widespread adoption and clinical translation. Here, we used Oct4, Sox2, Klf4, c-Myc driven pluripotency reprogramming to evaluate methods for enhancing and tailoring cell fate transitions, through directed evolution with iterative screening of pooled mutant libraries and phenotypic selection. We identified an artificially evolved and enhanced P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…For example, it was proposed that the cooperation between the HMG-containing Dichaete and the POU protein vvl occurs during Drosophila neurogenesis [49][50][51]. On the other hand, in vivo data (ChIP-seq) show that DNA-dependent formation of the Sox-Oct dimer is more typical for POUV-class proteins, while other POU factors prefer binding to DNA as homodimers [52][53][54][55].…”
Section: Pouv-class Originmentioning
confidence: 99%
“…For example, it was proposed that the cooperation between the HMG-containing Dichaete and the POU protein vvl occurs during Drosophila neurogenesis [49][50][51]. On the other hand, in vivo data (ChIP-seq) show that DNA-dependent formation of the Sox-Oct dimer is more typical for POUV-class proteins, while other POU factors prefer binding to DNA as homodimers [52][53][54][55].…”
Section: Pouv-class Originmentioning
confidence: 99%
“…Perhaps the apparent barrier is merely a testimony to the inadequacy of the wild-type factor-based reprogramming machinery, which we currently employ. We and others have reported engineering enhanced reprogramming factors that increased the efficiency of mouse reprogramming 31,106108 but none of the studies showed a substantial gain of efficiency and faithfulness of iPSC generation beyond the mouse model. All alternative cocktails that improved the developmental potential of mouse iPSCs also decreased the efficiency of reprogramming, making them impractical even if they did work for humans 22,66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies addressed uniqueness of Oct4 among POU factors by domain swapping and mutagenesis 20,39,48,106,113116 . We and others determined the importance of the Oct4-POU S , POU HD linker, and CTD domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 ), such as the POU-S domain residues D159 (POU29) required for the mOct4-mSox2 interaction and iPSC formation 53 , V166 (POU36) required for optimal reprogramming 49 and a gain-of-function mutation (T152R (POU22) ) identified in an enhanced POU (ePOU) 63 . In addition, multiple positions in the first helix of the linker region have been identified as important for reprogramming 49 , including positions N206 (POU76) , N207 (POU77) , N209 (POU79) , L210 (POU80) and Q211 (POU81) and another gain-of-function mutation (E208P (POU78) ) 63 . Simultaneous mutation of N206 (POU76) , N207 (POU77) , N209 (POU79) and L210 (POU80) abolishes OCT4-rescue activity 49 .…”
Section: Discussionmentioning
confidence: 99%